Effect of nano-SiO2 particles modified by 3-aminopropyltriethyloxy silane on mechanical properties and thermal stability of meta-aramid insulation paper. Issue 16 (2nd November 2021) - Li, Xu; Li, Zhiwei; Liu, Jinghong; Bai, Hao; Yuan, Xueshi; Shen, Yin; Luo, Xinxin; Xiong, Bifeng; Xie, Jingyu; Wang, Jingna; Tang, Chao
ABSTRACT : To further enhance the performance of nano-silica modified M-phenylene isophthalamide (MPIA) insulation paper, nano-SiO2 particles are modified by 3-aminopropyltriethyloxy silane (APTS) surface into meta-aramid insulation paper to form grafting nano-silica particles (GNP). In order to find the relative best performance of the nanoparticle doping ratio, molecular dynamics simulations were used to study the effect of different GNP volume fractions on the mechanical parameters of the MPIA amorphous region, and the highest mechanical performance was obtained with a volume fraction of 9.4 vol. %. Under this doping condition, the interaction between GNP and MPIA fibers was enhanced by the formation of a large number of hydrogen bonds. The addition of GNP decreased the diffusion of water, acid and gas in MPIA fibers and the influence of these substances on the thermal stability of aramid fibers. All these indicate that the addition of GNP further improves the performance of aramid insulation paper, improves the thermal stability of aramid insulation paper and delays the aging process of oil-immersed aramid insulation paper. This article provides a reference and basis for the preparation of meta-aramid insulation paper with relatively good thermal stability.